A Symmetrical Cross Double-D Coil with Improved Misalignment Tolerance for WPT Systems - Ashwini Rathod; Satish M. Mahajan; Taiye Owu (World Electric Vehicle Journal)
Inductive Wireless Power Transfer (WPT) technologies are advancing significantly in the electric vehicle (EV) charging applications. Misalignment between transmitting and receiving coils can considerably affect power transmission efficiency in WPT systems. Prior research involved power electronics as well as electromagnetic couplers. This work focuses on the coil design aspect of electromagnetic couplers. A relatively new concept of Symmetrical Cross Double-D (SCDD) type of the coil design is introduced specifically to maximize tolerance to misalignment while sustaining significant amount of power transferred. Mutual inductance was determined for the perfect alignment and misalignment positions of the SCDD coils. Mutual inductance obtained from the simulation was validated from the experimental measurements. The SCDD electromagnetic coupler demonstrated almost 2.5 times superior tolerance to misalignment of coils compared to the conventional circular coupler while maintaining at least 78% of maximum power transfer even at a lateral misalignment of 40 mm.